The Financing of Social Housing in Integrating Financial Markets: A View from Developing Countries. - Renaud, Bertrand (Urban Studies (Routledge))
The housing sector is the last major sector of the national economy for which analytical foundations for economic and financial policy evaluation have developed. However, the application of this analytical framework to international comparisons of housing policies or the evaluation of housing finance systems still lags considerably behind the strong foundations laid over the years for trade, finance or industry policy analyses. None the less, the era when improvisation and fragmented policy-making in housing and housing finance could be excused is well past. Today, there is a deep and expanding body of basic research and policy analysis that can be shared for the design of housing policies and housing finance institutions whether it is in the European Union or developing countries. Obviously, social and economic contexts as well as wealth levels differ greatly. Common analytical foundations can lead to very different prescriptions in countries where macroeconomic and financial policies, financial infrastructure, and urban laws policies and practices differ. In some countries, the institutions of the markets are so deep that we may no longer be fully aware of them. In others, they barely exist. Everywhere, the division of labour between public and private actions in both housing policy and housing finance is shifting. Like European countries, but at much lower levels of income and wealth, developing countries continue to seek growth with equity. However, those are countries where the majority of people are poor, cities are growing rapidly, public as well as private institutions are often weak and fiscal resources are severely constrained. In such environments, it seems to stand to reason that the financing of social housing should only be a subset of public concerns for the development of a safe and sound housing finance system that will be able to expand in step with urbanisation. The question addressed here is where the financing of social housing fits within the new world of housing finance. The search for alternative forms of housing finance for low-income groups cannot disregard overall trends affecting the financial sector and hope to be sustainable. It has become clear during the past two decades that there is no such thing as a homogeneous 'Third World' across which identical policies and instruments could be conveniently applied. This simplistic concept resulted from the Cold War, ignorance of distant foreign places and, in particular, of their specific human capital, laws, institutions and practices. The reality in housing finance, as well as in other areas of public policy, is that there are profound differences among the more than 180 advanced and developing countries that are now members of the World Bank. It is therefore important to think of housing finance as 'path-dependent' in the sense that any innovation will be shaped by past and current conditions. One can distinguish six broad types of housing finance systems. Their main features are briefly outlined here. In spite of such international diversity, the separation of subsidies from finance and the redesign of social housing finance programmes are everywhere a critical reference for the design and development of better housing finance systems.